Evaluation of the SH-SY5Y cell line as an in vitro model for potency testing of a neuropeptide-expressing AAV vector - Zanker, Jeanette; Hüser, Daniela; Savy, Adrien; Lázaro-Petri, Sara; Hammer, Eva-Maria; Schwarzer, Christoph; Heilbronn, Regine (Frontiers in Molecular Neuroscience, 2023)
Viral vectors have become important tools for basic research and clinical gene therapy over the past years. However, in vitro testing of vector-derived transgene function can be challenging when specific post-translational modifications are needed for biological activity. Similarly, neuropeptide precursors need to be processed to yield mature neuropeptides. SH-SY5Y is a human neuroblastoma cell line commonly used due to its ability to differentiate into specific neuronal subtypes. In this study, we evaluate the suitability of SH-SY5Y cells in a potency assay for neuropeptide-expressing adeno-associated virus (AAV) vectors. We looked at the impact of neuronal differentiation and compared single-stranded (ss) AAV and self-complementary (sc) AAV transduction at increasing MOIs, RNA transcription kinetics, as well as protein expression and mature neuropeptide production. SH-SY5Y cells proved highly transducible with AAV1 already at low MOIs in the undifferentiated state and even better after neuronal differentiation. Readouts were GFP or neuropeptide mRNA expression. Production of mature neuropeptides was poor in undifferentiated cells. By contrast, differentiated cells produced and sequestered mature neuropeptides into the medium in a MOI-dependent manner.